Analysis of Hydrological Response to Climate and Land Use Land Cover Changes in Jewha Watershed Using SWAT Model, Ethiopia - Dereje Gebrie Habte; Satishkumar Belliethathan; Tenalem Ayenew (Air, Soil and Water Research)
Climate and LULC changes can affect runoff. Water stress is a major problem in Ethiopia’s upper and lower parts of the Jewuha watershed. This study aimed to examine the long-term patterns of freshwater availability in the study area under climate and LULC changes by analyzing long-term climate data using SWAT models. The SWAT model was used to simulate the runoff data. Calibrating and validating SWAT results were done by selecting sensitive parameters in the watershed. The LULC change predicted for 2045, a climate change analysis of the years 1984 to 2015 is conducted. The result of the study showed that surface runoff increased by 30.34 m 3 /s in 2015 as compared with 1984 mainly due to the impact of LULC change. Additionally, climate change’s impacts on the runoff increased by 16.1 m 3 /s in 2015 compared to 1984. The LULC classes, including vegetation cover (Forest and shrubland), experienced a shift from 35.94% in 1984 to 27.32% in 2015. The agricultural sector, which was 38.01% in 1984, has changed to 50.43% in 2015. The prediction values of agriculture and grassland are 52.29% and 24.193% respectively. At the same time, the prediction value of shrubland decreased to 14.186% in 2045. In general, the hydrology of the Jewha watershed is influenced by LULC and climatic variability in a significant and combined way.